2003
DOI: 10.1352/0047-6765(2003)41<188:seoaad>2.0.co;2
|View full text |Cite
|
Sign up to set email alerts
|

Supported Employment Outcomes Across a Decade: Is There Evidence of Improvement in the Quality of Implementation?

Abstract: There is little question that the strategies used to improve supported employment outcomes, namely higher wages and higher levels of integration, have changed since the mid-1980s. Innovations of natural supports and employer leadership have helped increase the capacity of provider agencies and the business community to include people with disabilities in the workforce. This report is the sixth in a series that focuses on features of natural supports and its relationship to outcomes. Our purpose in this paper i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
23
0

Year Published

2007
2007
2019
2019

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(26 citation statements)
references
References 14 publications
3
23
0
Order By: Relevance
“…This is consistent with previous research indicating that women tended to work significantly fewer hours than men and that incomes were less for women, although not significantly so (Olson et al, 2000). Hours per week worked and wages earned for participants in this study were comparable with findings reported by Mank et al (2003). In the current study, participants experienced both voluntary and involuntary job terminations.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…This is consistent with previous research indicating that women tended to work significantly fewer hours than men and that incomes were less for women, although not significantly so (Olson et al, 2000). Hours per week worked and wages earned for participants in this study were comparable with findings reported by Mank et al (2003). In the current study, participants experienced both voluntary and involuntary job terminations.…”
Section: Discussionsupporting
confidence: 91%
“…A 1996-1998 South Carolina study of 7,750 individuals with DD demonstrated an employment rate of only 16.9% and a job loss rate of 28% during the 2-year study period (Moran, McDermott, & Butkus, 2001). Reports have suggested that job losses occur more often in certain employment categories (janitor/laundry/ cleaning, dishwasher/bus person, hostess/cashier, food preparation, and lawn maintenance), positions into which persons with DDs tend to be placed most often (Mank, Cioffi, & Yovanoff, 2003;Olson et al, 2001). Gender appears to significantly influence tenure in supported employment, although it did not influence income for persons with DD.…”
Section: Barriers To Obtaining and Maintaining Employmentmentioning
confidence: 99%
“…200,000 people with different disabilities were thus employed in the general labour market in 2005 through 'supported employment' (Lawhead 2005). The survey by Mank, Cioffi, and Yovanoff (2003) with 656 participants showed that disabled persons who were integrated in the workplace earned the same wages for the same working hours as non-disabled part-time employees. The most common areas of employment are gastronomy, maintenance work, janitorial work, and in office environments (Mank, Cioffi, and Yovanoff 2003).…”
Section: Integrative or Direct Vocational Integration Schemesmentioning
confidence: 99%
“…Individuals with ID working in competitive or SE are most likely to find jobs in food service, custodial work, manufacturing, clerical work and, in rural settings, agriculture. [31][32][33] On average, they work approximately 20 to 28 hours per week. 23,31,34 In SE, the mean hourly wage is usually close to or slightly above the federal minimum wage.…”
Section: Employment Outcomesmentioning
confidence: 99%